Social science research and conservation management in the interior Borneo: unravelling past and present interactions of people and forests - Eghenter, C.; Sellato, B.; Devung, G.S. (Center for International Forestry Research, 2003)
The Culture and Conservation Research Program in Kayan Mentarang National Park, East Kalimantan, constitutes a unique interdisciplinary engagement in central Borneo that lasted for six years (1991-97). Based on original ethnographic, ecological, and historical data, this volume comprehensively describes the people and the environment of this region and makes a rare contribution to the understanding of past and present interactions between people and forests in central Borneo. Kayan Mentarang has thus become one of the ethnographically best known protected areas in Southeast Asia. By pointing at the interface between research and forest management, this book offers tools for easing the antagonism between applied and scholarly research, and building much needed connections across fields of knowledge.